2020
DOI: 10.15244/pjoes/122805
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Diversity and Variation of <i>Lonicera caerulea</i> Populations in the Changbai Mountain Alongside the Elevation Gradient

et al.

Abstract: Plant phenotypic diversity is the product of the genetic diversity and ecological environment of a population and is mainly expressed in the morphological features of a population under different habitat conditions within its distribution area [1-3]. Phenotypic and functional traits are plastic in response to the environment, allowing plants to adapt to new habitats [4,5]. Changes in elevation gradients are associated with significant changes in ecology [6]. For instance, increased elevation is associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
1
0
1
Order By: Relevance
“…The average variance component among populations was greater than that within populations, which further indicated that the phenotypic traits of E. angustifolia in Gansu Province varied greatly, and the variation mainly came from populations. The phenotypic variation among populations was higher than that within populations, which was consistent with the results of analyses of Pinus sylvestris [36], Lonicera caerulea [37], and Haloxylon ammodendron [38]. This may be related to the geographical isolation of each population, which hinders the pollination of wind-pollinated plants and the gene exchange among populations and increases the differentiation among populations.…”
Section: Discussionsupporting
confidence: 86%
“…The average variance component among populations was greater than that within populations, which further indicated that the phenotypic traits of E. angustifolia in Gansu Province varied greatly, and the variation mainly came from populations. The phenotypic variation among populations was higher than that within populations, which was consistent with the results of analyses of Pinus sylvestris [36], Lonicera caerulea [37], and Haloxylon ammodendron [38]. This may be related to the geographical isolation of each population, which hinders the pollination of wind-pollinated plants and the gene exchange among populations and increases the differentiation among populations.…”
Section: Discussionsupporting
confidence: 86%
“…The average H of the 20 phenotypes was 1.82. It was lower than the H values reported for L. caerulea [40] (H > 2.00) and C. pinnatifida [41] (H > 4.49) and higher than that reported for E. japonica [42]. This indicates that L. cubeba still shows rich diversity, despite germplasm losses.…”
Section: Phenotypic Diversity Of L Cubeba Characteristicscontrasting
confidence: 66%